IMMUNE RESPONSE TO VACCINATION IN CHILDREN AND YOUNG PEOPLE WITH INFLAMMATORY BOWEL DISEASE: A 10 YEARS SYSTEMATIC REVIEW - Gumilang, Retna (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background:  In the past decade, there is a notable uptrend in the incidence of IBD among the pediatric population. The immunosuppressive nature of IBD treatment may compromise the natural immune response, potentially impacting vaccination effectiveness. This study aims to to provide a 10 year systematic review of post vaccination immune response in pediatric IBD patients.  Methods: This systematic review adhered to the PRISMA 2020 standards and included full-text English literature published between 2014 and 2024. Exclusion criteria involved editorials, review articles from the same journal, and submissions lacking a DOI. Literature was gathered from online sources such as PubMed and SagePub. Result: Our search in PubMed yielded 156 articles, while SagePub produced 243 articles. Focusing on the year 2014, PubMed had 127 articles, and SagePub had 102. Ultimately  we selected 6 papers that met our criteria, 3 from PubMed and 3 from SagePub. Conclusion:  This study concludes that the immunogenicity of certain vaccines such as PCV13, PPSV23, and rotavirus were not affected by the IBD, except for cholera. No adverse effect were found directly related to vaccination in pediatric IBD patients.